EVALUATION OF WORLD ENERGY SCENARIOS - V. I. Salygin; I. I. Litvinyuk (Vestnik MGIMO-Universiteta)
What are the future global systems developments? It remains one the biggest unknown, especially in terms of energy, as it is globally considered as both cause and solution for multiple problems of the humanity. Therefore, nowadays a number of experts are exploring driving forces, critical uncertainties and unknowns that have an influence on future energy systems development. This article aims at providing a brief investigation of existing world energy scenarios that cover the range of plausible outcomes of future global energy system development. Those are represented by International Energy Agency, World Energy Council, Organization of the Petroleum Exporting Countries, and others. The analysis covers both qualitative and quantitative indicators of the world energy system development that provide for future worldview formation. The article looks into various approaches to energy system development forecasting and scenario building employed by the abovementioned organisations, and discovers the motives for making assumptions as the means of attaining internal targets and the consequences of the distinction of individual attitude to the development trends within the expert community. The current assessment implies grouping of the most advanced of the existing energy system development models, identification their advantages and disadvantages, and shows differences in modeling approaches used in a number of specialized international organisations.